History of the International Symposium on Fungal Stress – ISFUS, a dream come true!. Issue 5 (May 2020) - Rangel, Drauzio E.N.; Alder-Rangel, Alene
Abstract: The International Symposium on Fungal Stress (ISFUS) was born in a dream that Drauzio Eduardo Naretto Rangel had in 2013. This article reviews the first three ISFUSs and prospects for the future meetings. Although ISFUS was born as a small family organized meeting, since the first meeting, ISFUS has achieved great success, receiving very important research grants from FAPESP, FAPEG, and CAPES to bring international scientists to Brazil. Moreover, three special issues in leading journals have been published with articles relating to the talks presented at each ISFUS. For the first meeting, most speakers published in a special issue in Current Genetics. From the second and third meeting, articles from the speakers were published in special issues of the top mycology journal, Fungal Biology, published by Elsevier on behalf of the British Mycological Society. Here we show that following the dreams with a full heart and adding lots of love, passion, and hard work can achieve success.